2003
DOI: 10.1097/01.brs.0000062354.26905.b8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Radiculopathy and Pain With Oxiplex/SP Gel After Laminectomy, Laminotomy, and Discectomy

Abstract: Oxiplex/SP Gel was easy to use and safe for patients undergoing unilateral discectomy. Greater benefit in clinical outcome measures was seen in gel-treated patients, especially those with severe leg pain and weakness at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 44 publications
0
49
0
1
Order By: Relevance
“…Six RCTs 66,73,78,84,89,106 compared surgery with intraoperative interventions and found no overall significant difference between treatment groups. Two studies 78,84 included patients with either chronic or acute sciatica and one 66 included patients who had had sciatica for longer than 3 months; the chronicity of sciatica was not reported in three studies.…”
Section: Pain Intensity At Short-term Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Six RCTs 66,73,78,84,89,106 compared surgery with intraoperative interventions and found no overall significant difference between treatment groups. Two studies 78,84 included patients with either chronic or acute sciatica and one 66 included patients who had had sciatica for longer than 3 months; the chronicity of sciatica was not reported in three studies.…”
Section: Pain Intensity At Short-term Follow-upmentioning
confidence: 99%
“…Two studies 78,84 included patients with either chronic or acute sciatica and one 66 included patients who had had sciatica for longer than 3 months; the chronicity of sciatica was not reported in three studies. 73,89,106 Three studies 73,89,106 were of moderate to good quality, with adequate randomisation in all three and allocation concealment in two. 73,89 Three studies compared disc surgery with chemonucleolysis: two were RCTs 85,88 and one was a concurrent cohort study (CCS).…”
Section: Pain Intensity At Short-term Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium chloride inducing ionic cross-links is added to the formulation to create stronger interaction between the components. This modification prolongs the permanence of the product in the body because carboxymethil cellulose is otherwise rapidly resorbed 19,24 . Previous studies using Oxiplex have shown a significant reduction in the degree of postoperative peridural fibrosis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Kim òà ñï³âàâòîðè [8] àíàë³зóâàëè ðåзóëüòàòè âèêîðèñòàííя àíòèàäãåзèâíîãî ãåëю «Medisheld» чåðåз 1 òà 6 м³ñ ó хâîðèх з ãðóбèм ïàðåзîм ñòîïè ³ âèðàaeåíèм бîëüîâèм ñèíäðîмîм.  11 ïàö³єíò³â ï³ä чàñ зä³éñíåííя м³êðîäèñêåêòî-м³¿ ââîäèëè ãåëü, ó 7 -ãåëü íå âèêîðèñòîâóâàëè.…”
Section: кëючîâ³ ñëîâà: компресійний рубцево-спайковий епідурит резуunclassified